ANALISIS VITAMIN C PADA BUAH JERUK PASAMAN UNTUK MENINGKATKAN IMUNITAS TUBUH PADA MASA PANDEMI : ANALISIS VITAMIN C - Vivi Sisca; Jumriana Rahayuningsih; Eliyarti Eliyarti (UIR Press, 2022)
Vitamin C is the best antioxidant known to have benefits to boost immunity. One of the fruits that contain vitamin C is the Pasaman orange. Pasaman orange is a fruit that is a flowering plant with members of the Citrus clan from the Rutaceae tribe (orange-orange tribe). Pasaman oranges were analyzed for their vitamin C content in order to increase the community's immunity during the covid-19 pandemic. The method used is a laboratory experiment with the iodometric method. The result is that Pasaman oranges contain high levels of vitamin C, with the average vitamin C levels in the Pasaman oranges being 10.22%, 11.18% and 10.38% respectively, while the average vitamin C levels in the Pasaman oranges were 10.59%. And during this pandemic, we should consume a lot of food and fruit with vitamin C to increase the body's immunity, so that it can be developed to the next stage of further and more effective research.